2023
DOI: 10.7150/thno.81893
|View full text |Cite
|
Sign up to set email alerts
|

Vertical sleeve gastrectomy-derived gut metabolite licoricidin activates beige fat thermogenesis to combat obesity

Abstract: Obesity is a chronic metabolic disease, affecting individuals throughout the world. Bariatric surgery such as vertical sleeve gastrectomy (VSG) provides sustained weight loss and improves glucose homeostasis in obese mice and humans. However, the precise underlying mechanisms remain elusive. In this study, we investigated the potential roles and the mechanisms of action of gut metabolites in VSG-induced anti-obesity effect and metabolic improvement. Methods: High-fat diet (HFD)-fed C57B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…Evidences from basic biological research and observational studies have identified poor socioeconomic factors (e.g., low income, low education, and a single civil status), unhealthy lifestyles (e.g., smoking, alcohol consumption, and unhealthy diet), and gut metabolite as important factors related to cardiometabolic multimorbidity (11)(12)(13)(14)(15)(16). Additionally, studies have explored the association between body measures, such as grip strength (17).…”
Section: Introductionmentioning
confidence: 99%
“…Evidences from basic biological research and observational studies have identified poor socioeconomic factors (e.g., low income, low education, and a single civil status), unhealthy lifestyles (e.g., smoking, alcohol consumption, and unhealthy diet), and gut metabolite as important factors related to cardiometabolic multimorbidity (11)(12)(13)(14)(15)(16). Additionally, studies have explored the association between body measures, such as grip strength (17).…”
Section: Introductionmentioning
confidence: 99%
“…While both gut microbiota and bariatric surgery have been shown to activate thermogenesis in fat [14], their connection has, until recently, not been addressed. Two new studies by Jin et al [15] and Yadav et al [16] now provide causal evidence, using complementary approaches, that VSG and RYGB activate thermogenesis in fat through distinct microbiota-dependent mechanisms, to in turn promote metabolic health.…”
mentioning
confidence: 99%
“…In the first study by Jin et al [15] VSG and sham surgery were performed on diet-induced obese mice. The authors found that VSG-operated mice displayed reduced body weight associated with increased oxygen consumption compared with sham-operated mice.…”
mentioning
confidence: 99%
See 2 more Smart Citations